2001
DOI: 10.1124/mol.60.5.907
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Acetaminophen Hepatotoxicity in Transgenic Mice Overexpressing BCL-2

Abstract: Mitochondria play an important role in the cell death induced by many drugs, including hepatotoxicity from overdose of the popular analgesic, acetaminophen (APAP). To investigate mitochondrial alterations associated with APAP-induced hepatotoxicity, the subcellular distribution of proapoptotic BAX was determined. Based on the antiapoptotic characteristics of BCL-2, we further hypothesized that if a BAX component was evident then BCL-2 overexpression may be hepatoprotective. Mice, either with a human bcl-2 tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 32 publications
5
73
0
Order By: Relevance
“…On the other hand bcl-x L another antiapoptotic gene more affected by APAP than bcl-2 in this cell, the mRNA of bcl-x L decreased after 6 h and dramatically decreased until 48 h, and over-expression of aldose reductase augmented APAPinduced reduction on bcl-x L . In consistent with that, previous studies demonstrated that transgenic mice overexpressing bcl-2 is more susceptible to APAP induced hepatotoxicity with massive panlobular necrosis by 24 h [20]. Moreover, administration of APAP to BALB/c mice caused extensive centrilobular apoptosis and necrosis, accompanied by up-regulation of anti-apoptotic protein bcl-2 after 24 h [21].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand bcl-x L another antiapoptotic gene more affected by APAP than bcl-2 in this cell, the mRNA of bcl-x L decreased after 6 h and dramatically decreased until 48 h, and over-expression of aldose reductase augmented APAPinduced reduction on bcl-x L . In consistent with that, previous studies demonstrated that transgenic mice overexpressing bcl-2 is more susceptible to APAP induced hepatotoxicity with massive panlobular necrosis by 24 h [20]. Moreover, administration of APAP to BALB/c mice caused extensive centrilobular apoptosis and necrosis, accompanied by up-regulation of anti-apoptotic protein bcl-2 after 24 h [21].…”
Section: Discussionsupporting
confidence: 89%
“…9 The role of Bcl-2 as a pro-oxidant protein in live animal models has also been reflected in other model systems. 10 If this scenario were indeed true, it would be of great interest to identify the cellular source(s) of superoxide…”
mentioning
confidence: 99%
“…Hallmarks of apoptotic cell death include several morphological features, such as cell shrinkage, chromatin condensation, and formation of apoptotic bodies as well as extensive caspase activation (60). In general, only very few apoptotic cells are detectable after APAP overdose (23), and there is no relevant caspase activation in mouse livers (23,52,61). Furthermore, pancaspase inhibitor did not protect against APAP hepatotoxicity (23-25, 52, 62, 63).…”
Section: Figurementioning
confidence: 99%